2016
DOI: 10.1186/s12348-016-0082-3
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral neuroretinitis and anterior uveitis following ipilimumab treatment for metastatic melanoma

Abstract: BackgroundThis report presents a novel case of bilateral neuroretinitis and anterior uveitis in a patient receiving ipilimumab treatment for metastatic cutaneous melanoma and summarizes the literature regarding treatment options for patients with ipilimumab-related ocular immune-related adverse events.FindingsThe medical chart was reviewed, a literature search was performed, and the results were summarized. For the case presented here, in addition to discontinuation of ipilimumab, combined topical and oral cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Several clinicians have reported on cases with ocular side effects of ipilimumab, with the typical cases of immune-related ocular side effects appearing to be similar to Vogt-Koyanagi-Harada-like syndrome 2,3. However, our current case did not have findings suggestive of Vogt-Koyanagi-Harada-like syndrome, nor did it have any typical angiographic findings which suggested the presence of central serous chorioretinopathy (CSC).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Several clinicians have reported on cases with ocular side effects of ipilimumab, with the typical cases of immune-related ocular side effects appearing to be similar to Vogt-Koyanagi-Harada-like syndrome 2,3. However, our current case did not have findings suggestive of Vogt-Koyanagi-Harada-like syndrome, nor did it have any typical angiographic findings which suggested the presence of central serous chorioretinopathy (CSC).…”
Section: Discussionmentioning
confidence: 52%
“…For example, systemic complications such as type Ⅰ diabetes, hypothyroidism, hypopituitarism, colitis and hepatitis have been reported. Ophthalmologic complications have also been reported and include iridocyclitis, optic neuritis,2 chorioretinitis and Vogt-Koyanagi-Harada-like syndrome with impaired hearing and vitiligo 3…”
Section: Introductionmentioning
confidence: 99%
“…However, with the advent of newer agents, the awareness and development of adverse event management are crucial . Of note, immune‐mediated uveitis has also been reported with nivolumab, another PD‐1 inhibitor, and ipilimumab …”
Section: Discussionmentioning
confidence: 99%
“…Adverse events usually manifest in the form of skin inflammation ( 191 195 ), gastrointestinal disorders ( 196 200 ), hepatic malfunction ( 191 , 196 ), respiratory complications ( 186 , 197 ), and endocrine disorders ( 191 , 198 ). Rare manifestations such as sicca syndrome and arthritis ( 199 ), ocular inflammation ( 197 , 200 , 201 ), nephritis ( 202 204 ), heart disease ( 197 , 205 ), and meningitis ( 206 ) also occur. Various case studies and clinical trials have demonstrated that there is less toxicity and prolonged progression-free survival from the use of PD-1 checkpoint blockade compared to CTLA-4, in advanced melanoma, for instance ( 187 , 207 ).…”
Section: Immune Checkpoint Blockadementioning
confidence: 99%